Determinants of Buying Interest in The Tiktok Shop Marketplace - Ramadhini, Assyifa Shafira; Sugiarti, Rina; Agustin, Sri Kurniasih (Lentera Ilmu Nusantara, 2024)
The existence of technological advances in the current economy is evidenced by the creation of marketplaces or online stores that can be accessed anytime, anywhere. TikTok Shop is one of the marketplaces that sells a variety of products to meet needs easily and quickly. The purpose of this study is to analyze the factors that affect buying interest in the TikTok Shop marketplace. The sampling method uses non-probability sampling with accidental sampling technique. The data source is primary data obtained by distributing questionnaires to 110 respondents which is measured through several indicators from each related variable. The test stages carried out are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F test and t test. The results showed that the electronic word of mouth variable had no effect on buying interest, while the price discount variable, online customer review, and trust had an effect on buying interest. Based on the results of the F Test, it shows that the variables electronic word of mouth, price discount, online customer review, and trust have a simultaneous effect on buying interest in the TikTok Shop marketplace. The variable that has the most dominant influence on buying interest is the belief variable.